2004
DOI: 10.1097/01.psy.0000116755.71033.10
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Trauma, Distress, and Posttraumatic Stress Disorder Among Breast Cancer Patients

Abstract: Although an intense negative emotional reaction to breast cancer was common, PTSD had low prevalence. Results suggest that using a trauma framework to understand the experience of most patients with cancer may be inaccurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 43 publications
5
94
0
10
Order By: Relevance
“…These consequences, whether post-traumatic symptoms, distress or loss of meaning, have been widely studied in many researches (Cordova et al, 1995;Cohen M., 2002;Palmer et al,2004).…”
Section: Introductionmentioning
confidence: 99%
“…These consequences, whether post-traumatic symptoms, distress or loss of meaning, have been widely studied in many researches (Cordova et al, 1995;Cohen M., 2002;Palmer et al,2004).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the available data come not from studies determining patients' syndromal or subsyndromal PTSD diagnoses, but from patient self-reports of traumatic symptoms found to be correlated with poor quality of life and/or impaired physical functioning (e.g., Diemling, Kahana, Bowman, & Schaefer, 2002;Jacobsen et al, 1998; for a review, see Kangas, Henry, & Bryant, 2002 (Gurevich et al, 2002;Kangas et al, 2002), only 8 studies used diagnostic interviews (e.g., SCID; First, Spitzer, Gibbon, & Williams, 1996). Across studies, 0 to 10 patients with PTSD were identified, for a total of 40 PTSD cases in the literature from over 700 patients assessed (Alter et al, 1996;Brewin, Watson, McCarthy, Hyman, & Dayson, 1998;Green et al, 1998;Kangas, Henry, & Bryant, 2005;Mehnert & Koch, 2007;Mundy et al, 2000;Palmer, Kagee, Coyne, & DeMichele, 2004;Pitman et al, 2001). Thus, a study of more cases of PTSD would be useful, but clarifying the clinical picture for those with subsyndromal PTSD would be of particular value.…”
Section: Introductionmentioning
confidence: 99%
“…Although survivorship is increasing, individuals diagnosed with cancer must navigate the processes of recovery. Although fewer than 10% meet criteria for a PTSD diagnosis, up to 67% of patients report symptoms of PTSD in the first year following cancer treatment (Kangas, Henry, & Bryant, 2002;Palmer, Kagee, Coyne, & DeMichele, 2004). Worry is also common, with 30% to 40% of cancer survivors reporting ongoing fears of recurrence and of diagnostic tests (Deimling, Bowman, Sterns, Wagner, & Kahana, 2006).…”
mentioning
confidence: 99%